2019
DOI: 10.1021/acs.orglett.9b00287
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Dual Annulation: A Method for the Synthesis of Norneocryptolepine

Abstract: A novel procedure for the Pd-catalyzed dual annulation reaction to synthesize the norneocryptolepine derivatives involving the concerted construction of two central heterocycles is reported. The further methylation of the norneocryptolepine to afford its alkaloid analog neocryptolepine implies that synthesis of various neocryptolepine derivatives is feasible. The oxidative addition of Pd(0) is indicated as the key step to activate the intramolecular addition of nitrile according to the mechanism study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…In 2019, we have reported the Pd-catalyzed tandem cyclization reaction for the synthesis of quinindoline core structures through the intramolecular addition of aniline to nitrile followed by N-arylation (Scheme 14). [19] This catalytic reaction can tolerate various substituents on the quinindoline scaffold and provide the desired products in high yields for most cases. We also found that this transformation can be executed in a copper/Lewis acid combined catalytic condition in slightly poor efficiency.…”
Section: Lewis Acid Accelerated Nucleophilic Addition Of Nitrilementioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, we have reported the Pd-catalyzed tandem cyclization reaction for the synthesis of quinindoline core structures through the intramolecular addition of aniline to nitrile followed by N-arylation (Scheme 14). [19] This catalytic reaction can tolerate various substituents on the quinindoline scaffold and provide the desired products in high yields for most cases. We also found that this transformation can be executed in a copper/Lewis acid combined catalytic condition in slightly poor efficiency.…”
Section: Lewis Acid Accelerated Nucleophilic Addition Of Nitrilementioning
confidence: 99%
“…As indicated, norneocryptolepine can be synthesized by either the palladium or the copper catalysis, and a subsequent meth-ylation of the norneocryptolepine leads to the neocryptolepine in a high yield. [19,20] Both of these two alkaloids are bioactive compounds. The norneocryptolepine was first isolated from the leaves of Justicia betonica in 2004, [21] which possesses several bioactivities.…”
Section: Lewis Acid Accelerated Nucleophilic Addition Of Nitrilementioning
confidence: 99%
“…A variety of late-transition-metals have been shown to possess the ability to form this intermediate for further transformations [ 5 , 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], which have been commonly indicated to construct six- or five-membered N -heterocyclic structures via the 1,2- or 1,1-insertion of molecules containing multiple bonds. For those revealed catalysts, the first-row transition-metal complexes exhibit comparably higher economic efficiency, and our continuing studies on cobalt-catalyzed coupling reactions [ 25 ], as well as the experiences in cyclization reactions [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], encouraged us to attempt the synthesis of diverse N -heterocyclic scaffolds by using the five-membered cobalacycle intermediate and switching different cyclization partners ( Scheme 2 ). Under this reaction concept, we were able to obtain several N -heterocyclic compounds, including indenoisoquinolinones, chiral 1-aminoindenes, and isoquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…The dual annulation of an N -alkynylaryl- N -aryl carbodiimide through diradical pathway is the third common strategy, but not as often recorded as other two routes [ 17 , 18 , 19 ]. Despite these three dominant pathways, there have been several modern strategies reported [ 11 , 12 , 13 , 20 , 21 , 22 ]. In this respect, our recent work in the synthesis of norneocryptolepine derivatives through a Pd-catalysis can systematically offer the unprotected quinindolines various substituents on the benzene moieties ( Scheme 1 ) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these three dominant pathways, there have been several modern strategies reported [11][12][13][20][21][22]. In this respect, our recent work in the synthesis of norneocryptolepine derivatives through a Pd-catalysis can systematically offer the unprotected quinindolines various substituents on the benzene moieties (Scheme 1) [22]. This work and our experience in the construction of heterocycles [23][24][25][26][27][28][29][30] encouraged us to continuously study in this field.…”
Section: Introductionmentioning
confidence: 99%